Revaluasi Aset Pada Perusahaan Perbankan Indonesia - Amir Hamzah; Lia Dwi Martika; Indriyani Indriyani (JRAK: Journal of Accounting Research and Computerized Accounting, 2023)
The purpose of this study was to determine the effect of Debt Contracts, Political Factors, and Information Asymmetry on Asset Revaluation. The research method used in this research is descriptive and verification methods. The population of this research is banking as many as 110 companies registered with the Financial Services Authority in 2018-2022. The method of determining the sample in this study used a purposive sampling method of 30 companies registered with the Financial Services Authority in 2018-2022. The analysis technique applied in this research is logistic regression analysis. The test results show that the Debt Contract, Political Factor, and Information Asymmetry simultaneously has a significant effect on Asset Revaluation. Leverage, Liquidity, Operating Cash Flow, Company Size, and Fixed Asset Intensity partially has a positive effect on asset revaluation.